A STUDY ON THE FINANCIAL PERFORMANCE, GROWTH, AND PROFITABILITY OF PRIVATE SUGAR INDUSTRIES IN TAMIL NADU - K. Komathi; N. Gunasekaran (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study examines the financial performance, growth, and profitability of private sugar industries in Tamil Nadu, which play a significant role in the state’s economy. The sugar industry is one of the largest contributors to employment, rural development, and industrial growth in Tamil Nadu. However, the performance of private sugar mills can be influenced by various factors, such as changes in sugar prices, government policies, and fluctuations in raw material costs. This study aims to assess the financial health, growth trends, and profitability of private sugar industries, with a focus on the impact of these factors. Through financial ratio analysis and performance indicators, this research evaluates the industry’s sustainability and its contribution to the state’s economy. The findings aim to provide valuable insights for industry stakeholders, policymakers, and investors to understand the financial dynamics of private sugar mills and suggest measures to improve their overall performance.